(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
Objective: The main objective is to account for the course of public policy in science and technology in Mexico, with special reference to the 2018-2024 government. Material and Method: Theory of social representation (Moscovici, 1979) in order to explain in detail what is published, transmitted or disseminated about S&T today. Discussion: The course of science and technology in Mexico is presented, bearing in mind its components, such as expenditure, institutional funds, fiscal incentives, human capital, institutional program. Conclusion: It is reported that science and technology have not been given special treatment in public affairs, neither has a State public policy on science and technology been configured.